The Influence of Work Discipline, Job Satisfaction and Work Environment on the Performance of Surabaya Region III Airport Authority Employees - Gita Ari Handayani; Sundjoto Sundjoto; Sri Rahayu (Journal of Education Technology Information Social Sciences and Health, 2024)
This research aims to determine the extent of the influence of work discipline, job satisfaction and work environment on the performance of employees of the Surabaya Region III airport authority. This type of research is quantitative. The type of data used in this research is primary data and secondary data. Secondary data is data obtained by the author indirectly, namely data from the Surabaya Region III Airport Authority office. The data analysis technique used in this research is multiple linear regression analysis. Based on the results of simultaneous testing of work discipline (X1), Job Satisfaction (X2) and Work Environment (X3) on Employee Performance (Y), the calculated F is 10,284 F table 2.76 with a significance of 0.000. Because the significance level is smaller than 0.05, it means that Work Discipline (X₁), Job Satisfaction (X₂), and Work Environment (X₃) together have a significant influence on employee performance. Work discipline is really needed by every employee, because it is a means to train the employee's personality so that they always show good performance. This is very important in influencing the performance of Surabaya Region III Airport Authority employees. With work discipline, satisfaction and a good environment, employees will feel comfortable at work and have a commitment to where they work.